Lowe Syndrome and Me: a co-creation video series connecting patients, caregivers, and researchers - Haugen, Theresa; Gallop, Jennifer L.; Doerflinger, Hélène (Frontiers in Cell and Developmental Biology, 2025)
Lowe syndrome (LS) is a rare genetic disorder leading to significant physical and cognitive impairments. Recognizing the need to bridge the gap between researchers and the LS community, a collaborative patient and public involvement (PPI) project, Lowe Syndrome and Me, was initiated. This initiative aimed to foster understanding, improve communication, and strengthen advocacy through a co-created video series. Researchers from the Gurdon Institute (United Kingdom) and caregivers from the Lowe Syndrome Association (United States) collaborated to develop a series of videos capturing the unique perspectives of patients and their families, advocacy group members, and researchers. Participants received video production and scriptwriting training, ensuring authentic representation and shared ownership of the content. The videos were disseminated through social media, research institute and patient group websites in the United States, United Kingdom and France, raising awareness and improving engagement within the LS community. Feedback from participants highlighted high satisfaction, increased understanding of research, and enhanced communication skills. Challenges included geographical barriers and limited participant diversity, but the project successfully fostered reciprocal learning and strengthened advocacy networks. This case illustrates how meaningful PPI can empower patient communities, enhance research relevance, and promote broader public awareness of rare diseases.